2004
DOI: 10.1039/b403191c
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of pyrrole: Evidence for mode specific dynamics from conical intersections

Abstract: The H and D atom elimination mechanisms in the photodissociation of jet cooled pyrrole and pyrrole-d1 have been studied by photofragment velocity map imaging. The molecules were excited to the 1 1A2 (pi sigma*) state at lambda = 243 nm and to the 1 1B2 (pi pi*) state at lambda = 217 nm. H/D atoms were detected by (2 + 1) resonance enhanced multiphoton ionization (REMPI) at lambda = 243 nm. The analysis of the images and the resulting translational energy distributions from the 1 1A2 state demonstrates the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(140 citation statements)
references
References 40 publications
12
127
1
Order By: Relevance
“…Most of experimental investigations on pyrrole photolysis have been performed either close to the band origin near 248 nm or at longer wavelengths near 193 nm [4][5][6]24,26]. The absorption cross section at the region of the long wavelength is only approximately 3 Â 10 À4 Å 2 molecule À1 , about 300 times smaller than at the short wavelength [2].…”
Section: The Uv Spectrum Of Pyrrolementioning
confidence: 99%
See 1 more Smart Citation
“…Most of experimental investigations on pyrrole photolysis have been performed either close to the band origin near 248 nm or at longer wavelengths near 193 nm [4][5][6]24,26]. The absorption cross section at the region of the long wavelength is only approximately 3 Â 10 À4 Å 2 molecule À1 , about 300 times smaller than at the short wavelength [2].…”
Section: The Uv Spectrum Of Pyrrolementioning
confidence: 99%
“…Photofragment spectroscopy has revealed the presence of the large fragments HCN, C 3 H 4 , C 3 H 3 , and CNH 2 in different fractions depending on the pump wavelength [4,5,26,27] The appearance of such fragments also seems to imply the existence of other internal conversion mechanisms occurring in competition with the NH-stretching. It has been proposed that such mechanisms would involve ring puckering [28] and ring opening [23,29] processes ( Fig.…”
Section: Introductionmentioning
confidence: 97%
“…12 The early PTS result was confirmed by a velocity map imaging (VMI) study of the H atoms from pyrrole photolysis at  = 243.1 nm. 13,14 Higher resolution TKER spectra of the H + pyrrolyl fragments formed following near UV excitation to the S 1 state of pyrrole show structure attributable to population of specific vibrational levels of the radical product. 15,16 The relative branching into these levels varies with photolysis wavelength, but all of the populated levels (apart from the v = 0 level) are found to involve non-totally symmetric nuclear motions.…”
Section: -8mentioning
confidence: 99%
“…Using photofragment translational spectroscopy (PTS), Blank et al found upon excitation at 193 and 248 nm that the H elimination channel is the main dissociation channel. 1 Later, higher energy-resolution experiments [4][5][6][7][8]15 in the wavelength range 193.3-254.0 nm observed two components in the H product translational energy distributions: a "fast" component with a higher, sharp kinetic energy distribution and a "slow" component with a lower, broad kinetic energy distribution. A picture was proposed as follows: upon the approach of the wavepacket to the conical intersection (CI) between the πσ * and ground states, the wavepacket either evolves to the ground state and results in a statistical dissociation of the hot ground state, leading to nascent H-atoms with lower kinetic energies, or evolves diabatically leading to a direct cleavage of the N-H bond to yield H-atoms with higher kinetic energies.…”
Section: Introductionmentioning
confidence: 99%